2014
DOI: 10.2139/ssrn.2560771
|View full text |Cite
|
Sign up to set email alerts
|

ICT and Economic Growth Comparing Developing, Emerging and Developed Countries

Abstract: This paper analyzes the impact of information and communication technologies (ICT) on economic growth in developing, emerging and developed countries. It is based on a sample of 59 countries for the period 1995 to 2010. Various panel data regressions confirm the positive relationship between ICT capital and GDP growth. The regressions for the subsamples of developing, emerging and developed countries do not reveal statistically significant differences of the output elasticity of ICT between these three country… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
100
1
8

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(111 citation statements)
references
References 51 publications
2
100
1
8
Order By: Relevance
“…The study of [4], based on data relative to upper-income developing and developed countries for the period 1994-2007, provide econometric evidence of the positive impact of ICT on economic growth in developed and developing countries. Finally, the paper by [5] reveals that ICT has positive impact on emerging, developing and developed countries taken as a whole. However, this positive effect disappears once regressions are made for the subsample of developing, emerging and developed countries.…”
Section: Glance On Studies Related To Internet Impact On Economic Growthmentioning
confidence: 95%
“…The study of [4], based on data relative to upper-income developing and developed countries for the period 1994-2007, provide econometric evidence of the positive impact of ICT on economic growth in developed and developing countries. Finally, the paper by [5] reveals that ICT has positive impact on emerging, developing and developed countries taken as a whole. However, this positive effect disappears once regressions are made for the subsample of developing, emerging and developed countries.…”
Section: Glance On Studies Related To Internet Impact On Economic Growthmentioning
confidence: 95%
“…Hettiarachchi (2018) observed that information and communication technologies are usually overhyped and, however, are simply marketing impulses used by developed countries of the world to further enrich themselves, exploiting the developing nations. Niebel and Mannheim (2014) analysed the impact of ICT on economic growth in developing, emerging and developed countries. The sample base comprised of 59 countries within the period of 1995 to 2010.…”
Section: Brief Review Of Related Literaturementioning
confidence: 99%
“…Liu, Jr. Chen, C. Huang, C. Yang [2], M. Lund, S. McGuire [3] the impact of e-commerce and R&D on economic development and productivity is proved. E. Karlsson, J. Liljevern [4], A. Yousefi [5], T. Niebel [6], F. Venturini [7] in their papers came to the conclusion that there is a positive relationship between the use of the Internet, ICT and increased productivity. In addition, research findings, which were covered in the papers of Z. Hossain, M. Ishaq Bhatti, Z. Ali [8], T. Pham, D. Nguyen [9], at the firm level show that ICTs can help increase the efficiency of enterprise management.…”
mentioning
confidence: 99%